Clausewitz és az Első Világháború = Clausewitz and the Great War - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2017)
Although Carl von Clausewitz wrote his works in the early 19th century, his ideas have signifi cantly infl uenced events of the 20th century, including the two World Wars. Vom Kriege (On War), Clausewitz’s fundamental work on military science became popular soon after its fi rst edition was published (1832-1834), and it pervaded not only military thinking but also political philosophy and politician thinking. Both the military and political professions were primarily interested in Vom Kriege in the context of the relationship between war and politics. However, as the work is incomplete and the author intended to revise it before his death, certain passages of the text can easily be interpreted or misinterpreted in various ways. As a result, Clausewitz’s theses became signifi cantly distorted in political and military practices during the century preceding the Great War. These distortions were partly due to changes in military practices following the Napoleonic wars and the emergence of modern mass armies numbering in the millions by the end of the century. Although there were some theories for how to wield these armies, soldiers and politicians lacked the necessary experience with their use. Thus, the powers at war started the Great War with the intent of a speedy resolution and carefully planned short-term military operations, which could only have been hindered by the interference of politics. Carrying out these military plans required disciplined and focused military leadership, which positioned soldiers as the leading force on both sides, while at the same time the supremacy of politics was generally accepted. This situation was clearly controversial and could only be resolved by militarizing politics. When the focus of the Great War shifted from the front lines to the potential of the opposing powers, it became diffi cult for people to understand the situation in its complexity. The opposing societies became exhausted, and the world confl ict could only be brought to a close from a military standpoint, while nobody was able to win the following peace. Thus, Clausewitz’s conceptions – which seemingly all parties had acted on– became signifi cantly distorted during the war and determined its events in such a skewed way.